The Effect of Court-Ordered Hiring Quotas on the Composition and Quality of Police - McCrary, Justin (American Economic Review, 2007)
Arguably the most aggressive affirmative action program ever implemented in the United States was a series of court-ordered racial hiring quotas imposed on municipal police departments.My best estimate of the effect of court-ordered affirmative action on workforce composition is a 14 percentage point gain in the fraction African American among newly hired officers.Evidence on police performance is mixed.Despite substantial black-white test score differences on police department entrance examinations, city crime rates appear unaffected by litigation.However, litigation lowers slightly both arrests per crime and the fraction black among serious arrestees.